Towards understanding economic growth in Africa: A reinterpretation of the Lewis Model - Diao, Xinshen; McMillan, Margaret S. (International Food Policy Research Institute, 2014)
Africa’s recent economic growth is at a historical high, the patterns associated with this growth appear to be quite different from the Asian experiences where rapid growth was fueled by labor intensive, export-oriented manufacturing. Because this pattern differs with our typical view of structural transformation, a heated debate has begun over the sustainability of Africa’s growth. In our view, Africa’s recent growth is still not well understood and thus it is difficult to say much that is meaningful about future prospects for growth on the continent. Against this background, we adapt Lewis’s (1954) dual-economy model to the economies of Africa to better understand the role that the “in-between” sector as defined by Lewis (1979) has played in Africa’s recent growth. Our framework incorporates the coexistence of a closed and an open modern economy and takes into account the diversity and heterogeneity of the activities that characterize modern African economies.